Pelayanan Pembuatan Izin Mendirikan Bangunan (IMB) Paten di Kantor Kecamatan Banjarmasin Utara Kota Banjarmasin - Linda Poernamasari (CV. Syntax Corporation Indonesia, 2022)
Purpose of this research was to know how the permit building service in north banjarmasin sub-district office of banjarmasin city and factors that can inhibit the permit building service in north banjarmasin sub-district office of banjarmasin city. Focus of this research was public servise dimension, this consepthas corellation to tangible of service, reability of employee, Responsiveness, assurance, and also emptahy of the employee. Method of this research was qualitative aproach with descriptive type. Data has been collected by observation, interview and documentation. The informans of this research were the head of north banjarmasin sub district, the employee of permit building service in north banjarmasin sub-district office of banjarmasin city and some of public figure. Result of this research decribe that the permit building service in north banjarmasin sub-district office of banjarmasin city has already good caused the facility has been served and quite re-presentative also skills of employee to give suitable service with what the society need. A few thing that should be improved to optimalizing the permit building service in north banjarmasin sub-district office of banjarmasin city. Such as: digitalizing information to facillitate information access to society and also improved the employee responsiveness to give permit building service in north banjarmasin sub-district office of banjarmasin city